2012
DOI: 10.5114/pwki.2012.29658
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis joint triggered recurrent anterior myocardial infarction in an adolescent taking dual anti-platelet therapy

Abstract: A b s t r a c tCannabis smoking has been rising world-wide especially in industrialized western countries. It has been known that cannabis use has adverse effects on the heart and vascular system and an increased risk of acute myocardial infarction (AMI) has been reported. The actual mechanism of cannabis-related AMI is not well known. In this report, we describe an adolescent with cannabis-induced recurrent left anterior descending coronary artery thrombosis and anterior myocardial infarction even on dual ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Results showed that, in the 60 min following marijuana smoking, the risk of MI onset is increased by 4.8 times over baseline (95% confidence interval, 2.4 to 9.5; p < 0.001), with a rapid decline in the risk thereafter. Consistent with these results, several cases reported an incidence of myocardial ischemia or infarction that is temporally associated with cannabinoid consumption [64][65][66][67]. The potential mechanisms underlying the transient elevated risk of MI post cannabinoid smoking are not fully understood; however, cannabinoid smoking is associated with rapid absorption of cannabinoids through the lung circulation, and the concentration of these compounds can reach peak levels in the systemic circulation within 30 min after smoking.…”
Section: Procoagulatory Effects Of Cannabinoidsmentioning
confidence: 60%
See 1 more Smart Citation
“…Results showed that, in the 60 min following marijuana smoking, the risk of MI onset is increased by 4.8 times over baseline (95% confidence interval, 2.4 to 9.5; p < 0.001), with a rapid decline in the risk thereafter. Consistent with these results, several cases reported an incidence of myocardial ischemia or infarction that is temporally associated with cannabinoid consumption [64][65][66][67]. The potential mechanisms underlying the transient elevated risk of MI post cannabinoid smoking are not fully understood; however, cannabinoid smoking is associated with rapid absorption of cannabinoids through the lung circulation, and the concentration of these compounds can reach peak levels in the systemic circulation within 30 min after smoking.…”
Section: Procoagulatory Effects Of Cannabinoidsmentioning
confidence: 60%
“…In addition to the indirect anticoagulatory effects of phytocannabinoids, some of them indeed have been shown to exhibit anticoagulatory effects in pre-clinical studies by inhibiting thrombin activity [12,52] or platelet aggregation [53,57]. It seems, however, that consuming phytocannabinoids (or sometimes synthetic ligands) by smoking is likely to be associated with procoagulatory effects [58,59,63,66,67]; whether smoking itself is responsible for inducing the procoagulatory effects of these cannabinoids remains to be elucidated. Reported coagulatory studies of endogenous cannabinoids have been mainly done in vitro and, except for one study that demonstrated an anticoagulatory effect of AEA by inhibiting platelet aggregation [57], most of these studies support a procoagulatory effect through stimulating platelet activation and aggregation, although the exact mechanisms by which this effect occurs are still controversial [72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, according to the American Heart Association, 18% of men and 35% of women undergo recurrent MI during 6 years after acute coronary syndrome, moreover 22% of men and 46% of women become disabled due to development of severe heart failure (HF), and 30-40% of patients develop left ventricular (LV) dysfunction [12]. This problem affects the low and middle income countries [13][14][15][16]. More than 80% of deaths from cardiovascular diseases occur in these countries almost equally among men and women.…”
mentioning
confidence: 99%